Editor's Comments - Terry Sefton (University of Windsor, 2013)
The Journal of Teaching and Learning focuses on issues of teaching and learning - obviously. However, teaching and learning are anything but straightforward, in all their many permutations and implications in school and in life. In this issue, each article approaches teaching and/or learning from a different vantage point: from the view of teachers, of teacher candidates, of school students, of administrators, ministries of education, and curriculum designers, in Canada, Africa, and Asia. Despite the apparent diversity of this collection, the articles contain many areas of overlap and points of convergence. While taking the Journal of Teaching and Learning online, and providing open access has been a great boon to our ever-increasing readership, I wonder, "What are we missing?" What has been lost, from the days when we sat down with a hard copy in our hands, started by scanning the table of contents, and then dove in, reading articles willy-nilly, in or out of order? I encourage you to read more than one of the articles in this issue, and to read 'across' for meanings that can be found between texts.